Vanishing social classes? Facts and figures of the Italian labour market - Armanda Cetrulo; Angelica Sbardella; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper analyses medium-term labour market trends from 1983 to 2018 in Italy relying on the "Rilevazione dei contratti di lavoro" from INPS archive which provides information on average salaries by professional category, age, gender, and geographical origin. Within an overall pattern of exacerbated inequalities, documented by means of different indicators, the empirical analysis highlights how the within-component of the wage variation prevails in the gender, age and geographical dimensions. By contrast, the between-component in terms of professional categories (trainees, blue-collar jobs, white-collar jobs, middle managers, executives) is the only between-variation attribute to prevail, corroborating the role played by class schema in explaining wage inequality. Regression-based inequality estimations confirm the role played by social classes. Stratification of wage losses is recorded being largely concentrated among blue-collar professional categories, women, youth, and in the Southern regions.
Keywords: E24; J31; J50; 330; Inequality; wages; occupations